Review of the Utilization of Natural Fibers and Polylactic Acid for Composite Manufacturing - Nugroho, Akhmad Andriyan; Fitri, Muhammad (Universitas Mercu Buana, 2026)
Composites made from polylactic acid (PLA) and natural fibers offer a sustainable alternative material that is biodegradable and derived from renewable sources. This review journal examines processing techniques, types of material testing, and the enhancement of the capabilities of natural fiber PLA composites to determine their potential applications as a substitute for conventional materials. From existing research journals discussing PLA and Natural Fiber-based composite materials with applications in various sectors, such as automotive, manufacturing and healthcare, it is known that the commonly used processing techniques are hot pressing and vacuum bagging to produce homogeneous fiber distribution and strong matrix-fiber bonds. Material testing is carried out through tensile tests, elastic modulus, and elongation to evaluate the mechanical properties of the composites. The results also show an increase in mechanical ability of 25-35% compared to pure materials, with fiber surface modification that can improve interfacial adhesion. PLA and natural fiber composites provide a sustainable material solution with competitive mechanical performance. Further research is needed to develop environmentally friendly fiber surface modification methods and scalable manufacturing techniques to expand industrial applications.